The nature and history of the Qilian Block in the context of the development of the Greater Tibetan Plateau - Huang, H.; Niu, Yaoling; Nowell, G.; Zhao, Z.D.; Yu, X.H.; Mo, X.X. (Gondwana Research, 2015)
The Palaeozoic granitoids in the Qilian Block are important for understanding the tectonic evolution of the Northern Tibetan Plateau. We choose granitoids from Huangyuan (HY) and Gangcha (Gcha) for a detailed study. The granitoids are S-type and I-type, and record different magmatisms from the Neoproterozoic to the Palaeozoic. Most samples have an emplacement age of 450 Ma with three samples being significantly older (924 Ma, 797 Ma and 503 Ma). The 924 Ma and 797 Ma magmatisms represent crustal growth and crustal reworking, respectively. The 503 Ma plagiogranite-like granite carries mantle isotope signatures and resulted from extensive fractional crystallization of mantle-derived melt in a back-arc setting. The 450 Ma granitoids have various chemical compositions, but most of them share similar trace element patterns resembling the bulk continental crust composition. Despite their large compositional and age variations, significant correlations on SiO2-variation diagrams and in isotope spaces suggest that these granitoids are different products essentially derived from common sources. The significant mantle contributions (70%–80%, apart from QL09-02) required by whole rock Sr–Nd–Pb–Hf isotopic compositions strongly suggest the “mantle source” as last fragments of the subducted/underthrusting oceanic crust at the onset of collision. Based on all the petrology, geochronology, geochemical data and adjacent tectonic associations, we suggest that the Qilian Ocean started opening in the Neoproterozoic between the Qaidam Block and the Qilian Block. A back-arc basin was developed between the Qilian Block and the Alashan Block shortly after. The 450 Ma granitoids are the products in response to the closure of the Qilian Ocean and the onset of the Qilian–Qaidam continental collision.
Keywords: Syn-collisional magmatism; I-; S-type granitoids; Crust growth; The Qilian Block; The Qilian Ocean.